The Concept of a Soul Mate in the Perspective of Tafsir al-ibriz - Safitri, Lutfi Dewi (Nizham Jurnal Studi Keislaman, 2023)
This paper discusses the concept of mate to be used by using Perspective of Tafsir al-Ibriz by Bisri Mustofa by revealing it in endeavor of Design mate to become a contribution of knowledge and scientific tafsir. Because currently it is necessary to have much knowledge about the mate to minimize the level of disputes in the wedding and lower the divorce rate. This paper is included in library research that originated from data collection in the form of books, articles and journal documents related to mate. Through the Maudhu'i approach by collecting verses about the mate and attracted concrete conclusions with the theme of the concept of the mate. The formulation of the problem in this study is what is the concept of a soul mate in the perspective of tafsir al-Ibriz and how relevant it is in the effort to design a soul mate. Based on the results of research, literature data and the set of Qur'anic verses with the keyword zawj answered the formulation of the problem that two concepts of mate were found two concepts of the mate in the Qur'an based on the interpretation of KH. Bisri Mustofa on the interpretation of al-Ibriz is the concept of mate is a soul mate by Surah al-a'rāf [7]:189, Surah An-Nisā '[4]:1, Surah an-naḥl [16]:72, Surah ar-Rūm [30]:21 and the second concept of the mate is fate by the Surah Aż-żāriyāt [51]:49, Surah An-Naba' [78]:8 and Surah Fāṭir [35]:11. What is revealing in the diabling design of the mate with an endeavor to improve yourself and to create yourself in the best version. As an effort to get good mate as with the desired pair. That is with four steps to improvement. First intention, second self-preservation, third adorned with the science, and the fourth keep the strap of the Silaturahmi.